Preliminary data of potentially hazardous radon concentrations in Modrič Cave (Croatia) - Robert Lončarić; Vanja Radolić; Maša Surić; Igor Miklavčić; Matea Šatalić; Dalibor Paar; Lukrecija Obšivač (International Journal of Speleology, 2023)
Instigated by relatively high cave-air CO2 concentrations in Modrič Cave (Croatia) recorded for the purpose of speleothem-based paleoclimate research, we established preliminary monitoring of radon (222Rn) concentrations within the cave for a 4.5-year period (2018–2022). As radioactive geogenic gas, radon, which often correlates with cave-air CO2 concentrations, presents a potential health hazard in cases of longer exposure time in high concentration conditions. Since the Modrič Cave is open to tourists and long-term scientific research has been performed within, a safety assessment for radon concentrations was essential. The integrated measurements of radon concentrations were performed by passive LR115 detectors that were exposed from three to six months at eight sites within the cave. Preliminary results showed seasonal variations of radon concentrations (0.08–13.6 kBq/m3) governed by the cave ventilation patterns, but superimposed on this, cave morphology and bedrock architecture control the radon variations on finer spatial scale. The 3-months average 222Rn concentration of up to 13.6 kBq/m3 during summer in one of the cave passages is among the highest measured seasonal averaged radon concentrations in Croatian caves, but maximum concentrations were even higher. Based on obtained results and calculations, potential negative health effects of radon exposure for cave visitors, guides and scientists were assessed and the results showed values of exposure to be below recommended levels. Calculated worst-case scenario for cave guides (most affected by radon and its progeny) revealed that they would receive dose slightly below the occupational dose limit of 20 mSv/y (19.0 ± 5.2 mSv/y) in the touristic part of the cave and significantly higher doses (34.1 ± 9.2 mSv/y) in the non-touristic part of the cave. To detect precise spatio-temporal radon concentration variations (up to diurnal scale) we recently established continuous radon measurements. This will enable detection of possibly health threatening short-term peaks in radon concentration and consequently further improve cave management.